Using a person-generated mental health outcome measure in large clinical trials in Kenya and Pakistan: Self-perceived problem responses in diverse communities. (February 2020) - Harper Shehadeh, Melissa; van't Hof, Edith; Schafer, Alison; van Ommeren, Mark; Farooq, Saeed; Hamdani, Syed Usman; Koyiet, Phiona; Akhtar, Parveen; Masood, Aqsa; Nazir, Huma; Dawson, Katie; Albanese, Emiliano
Health care should be informed by the physical, socioeconomic, mental, and emotional well-being of the person, and account for social circumstances and culture. Patient-generated outcome measures can contribute positively to mental health research in culturally diverse populations. In this study, we analysed qualitative responses to the Psychological Outcome Profiles (PSYCHLOPS) Questionnaire—a patient-generated outcome measure based on open-ended questions, and compared the qualitative responses gathered to conventional, nomothetic measures used alongside the PSYCHLOPS in two studies. Data were collected as part of outcome research on a psychological intervention in Pakistan ( N = 346) and Kenya ( N = 521). Two researchers coded the qualitative responses to the PSYCHLOPS and identified overarching themes. We compared the overarching themes identified to the items in the conventional, nomothetic outcome measures to investigate conceptual equivalence. Using the PSYCHLOPS, the most frequently reported problems in Kenya were financial constraints, poor health, and unemployment. In Pakistan, the most frequent problems were poor health and emotional problems. Most of the person-generated problem concepts were covered also in nomothetic measures that were part of the same study. However, there was no item equivalence in the nomothetic measures for the most frequent PSYCHLOPS problem cited in both countries. Response bias and measurement bias may not be excluded. More research on the use of PSYCHLOPS alongside conventional outcome measures is needed to further explore the extent to which it may bring added value. Use of a PSYCHLOPS semistructured interview schedule and efforts to minimise response biases should be considered.